Feeling like different persons: Becoming English teachers through overseas teaching internships - Isna Agustin; Nurfitri Longdaeva; Elok Putri Nimasari; Ana Maghfiroh (Englisia: Journal of Language, Education, and Humanities, 2026)
This study examines the professional identity development of Indonesian pre-service English teachers during a short-term international teaching internship in Southern Thailand, specifically exploring how participants perceived themselves as becoming "different persons" through this intercultural experience. Although existing research has established the role of intercultural encounters in shaping teacher identity, limited attention has been directed toward understanding how brief yet intensive overseas teaching placements contribute to emerging professional identities through processes of reflective meaning-making. Employing a collaborative narrative inquiry approach, the study analyzed written reflective narratives and semi-structured interview data collected from six Indonesian pre-service English teachers. The analysis focused on how professional identity construction unfolded through participants' everyday intercultural classroom experiences. The findings reveal that participants experienced substantial shifts in professional self-understanding, evidenced by expanded intercultural awareness, negotiated emotional and pedagogical challenges, and the development of adaptive teaching practices in response to unfamiliar classroom norms, multilingual interactions, and local school expectations. Critically, identity development did not result from intercultural exposure alone but emerged through sustained, reflective engagement with intercultural encounters throughout the internship period. This study contributes to the field of English language teacher education by highlighting the pedagogical and affective value of short-term international teaching internships and underscoring the necessity of structured intercultural preparation, guided reflection, and robust institutional support in fostering pre-service teachers' professional learning.